Written verbal fluency in normal aging with subjective memory complaints and mild cognitive impairment - Ruiz Sánchez de León, José María; Moratilla Pérez, Iván; Llanero Luque, Marcos (Anales de Psicología / Annals of Psychology, 2011)
Introduction. The present study analyzes whether a written verbal fluency task is suitable to differentiate between Mild Cognitive Impair-ment (MCI) and Normal Aging with subjective memory complaints (NA). Method. 140 subjects with a clinical judgement of NA (n=64) and MCI (n=76), diagnosed ad hoc, were administered both a verbal phonological fluency task and a verbal semantic fluency task. Results. The descriptive analysis of the data shows a homogeneous distribution of both groups taking into account age, gender and education. The group with NA scores significantly higher than the group with MCI on every indivicual criterion of evocation and also on both the summation of the three phonological criteria (FAS) and the summation of the three semantic criteria (SEMAN-TIC), being F=1.899, p<.005, for FAS and F=24.200, p<.001, for SE-MANTIC. The study also analyzes the correlations of the written verbal tasks with several classical screening tests. Discussion. The results support the suitability of the written verbal fluency tasks on the screening of MCI. Further, this assessment procedure offers, too, the benefit of its possibility of administration to a group of people. Differences between the phono-logical evocation criteria and the semantic evocation criteria were con-firmed in this study, concluding that the latter are more reliable at the screening of people with MCI than the former.